2021
DOI: 10.1186/s12909-021-03050-7
|View full text |Cite
|
Sign up to set email alerts
|

E-learning in medical education during COVID-19 pandemic: experiences of a research course at Kenya Medical Training College

Abstract: Background E-learning has been widely adopted as a teaching and learning approach in medical education internationally. However, its adoption in low- and middle-income countries is still at an infantile stage. The use of e-learning may help to overcome some of the barriers to access to quality education and provide flexible, low-cost, user-centred, and easily updated learning. To address the need for research education during the COVID-19 pandemic, we developed and implemented an e-learning cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Consequently, this study aims to assess non-medical HCP academic staff perceptions regarding the current challenges of Covid-19 on online teaching systems. This builds on the earlier study regarding dental and medical education in Bangladesh following the closure of universities in Bangladesh and similar studies in other LMICs 16,19,21,31,43 .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Consequently, this study aims to assess non-medical HCP academic staff perceptions regarding the current challenges of Covid-19 on online teaching systems. This builds on the earlier study regarding dental and medical education in Bangladesh following the closure of universities in Bangladesh and similar studies in other LMICs 16,19,21,31,43 .…”
Section: Introductionmentioning
confidence: 60%
“…It has been reported that Bangladesh and many other LMICs had limited experience with online learning at the start of the Covid-19 pandemic among academic staff and students and poor internet access, and high prices for the internet 19,21,29 . Other studies have revealed that improved faculty training on e-learning among LMICs, students supported financially to purchase the necessary equipment and internet bundles, launching Covid-19 prevention protocols including providing protective equipment, video-recorded lectures, tutorials to make up for a lost time, and simulated methods to teach clinical aspects, have all helped address identified barriers, with hybrid approaches to learning likely to stay 19,21,[30][31][32] . Other identified issues include addressing stress and mental health issues 16,19,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Users of the campus network use it to access services such as the Internet, e-learning platforms, internal financial systems and other collaboration platforms (Favale et al, 2020). Campus networks can assist in fighting pandemics such as COVID-19 by providing workingfrom-home platforms and e-learning services (Mahyoob, 2020;Gachanja et al, 2021). Basheeruddinasdaq et al (2021) argue that wireless technology in a campus network can facilitate fighting a pandemic by monitoring social distance and body temperature.…”
Section: Campus Network: An Overviewmentioning
confidence: 99%
“…Currently, campus networks face management challenges due to increased network services required by users, varying QoS for different traffic types, increased traffic volumes and device heterogeneity (Kim et al, 2021a, b). As stated by Gachanja et al (2021), the outbreak of pandemics such as COVID-19 requires a flexible environment which enables students to continue learning even from remote areas. Such situations trigger the requirement for flexible, manageable networks.…”
Section: The Automation Problem In Campus Networkmentioning
confidence: 99%
“…The Kenya Medical Training College (KMTC) has a network of 71 campuses, strategically located across the country in 45 out of 47 counties [ 24 ]. It offers pre-service nursing/midwifery and clinical officer training across the country [ 24 ] in various health care disciplines [ 25 ].…”
Section: Introductionmentioning
confidence: 99%